The influence of financial attitude, financial knowledge, andi individual income on financial management behavior of millennial generation in special capital region of Jakarta - Ayu Rizki Nurfadillah; Rindang Matoati (STIE Binaniaga, 2021)
The current era of globalization can have various impacts that can affect a person's behavior, namely financial behavior (behavior finance) in the millennial generation in Jakarta Special Capital Region. The millennial generation has a stigma that tends to be extravagant, difficult to save, has a high lifestyle, and is also consumptive, thus showing the millennial generation does not yet have good financial management behavior. This research aims to analyze the effect of financial attitudes, financial knowledge, and individual income on the financial management behavior of millennials in Jakarta Special Capital Region. The sampling technique was conducted using non-probability sampling with purposive sampling method. The data analysis method used is SEM-PLS analysis. The results of this research indicate that financial attitudes,and financial knowledge has a positive and significant effect on the financial management behavior of the millennial generation in DKI Jakarta, and for individual income it has no significant effect on the financial management behavior of the millennial generation in DKI Jakarta